(untitled) (Journal of Computational Mathematics, 2018)
An optimal control problem governed by the Stokes equations with L^2-norm state constraints is studied. Finite element approximation is constructed. The optimality conditions of both the exact and discretized problems are discussed, and the a priori error estimates of the optimal order accuracy in L^2-norm and H^1-norm are given. Some numerical experiments are presented to verify the theoretical results.